NB housing study protocol: investigating the relationship between subsidized housing, mental health, physical health and healthcare use in New Brunswick, Canada - J. Woodhall-Melnik; J. R. Dunn; I. Dweik; C. Monette; E. Nombro; J. Pappas; A. Lamont; D. Dutton; S. Doucet; A. Luke; F. I. Matheson; R. Nisenbaum; et al. (BMC, 2022)
Abstract Background Income and housing are pervasive social determinants of health. Subsidized housing is a prominent affordability mechanism in Canada; however, waitlists are lengthy. Subsidized rents should provide greater access to residual income, which may theoretically improve health outcomes. However, little is known about the health of tenants who wait for and receive subsidized housing. This is especially problematic for New Brunswick, a Canadian province with low population density, whose inhabitants experience income inequality, social exclusion, and challenges with healthcare access.  Methods This study will use a longitudinal, prospective matched cohort design. All 4,750 households on New Brunswick's subsidized housing wait list will be approached to participate. The survey measures various demographic, social and health indicators at six-month intervals for up to 18 months as they wait for subsidized housing. Those who receive housing will join an intervention group and receive surveys for an additional 18 months post-move date. With consent, participants will have their data linked to a provincial administrative database of medical records.  Discussion Knowledge of housing and health is sparse in Canada. This study will provide stakeholders with a wealth of health information on a population that is historically under-researched and underserved.